Combining patient talk about internet use during primary care consultations with retrospective accounts. A qualitative analysis of interactional and interview data - Stevenson, FA; Seguin, M; Leydon-Hudson, G; Barnes, R; Ziebland, S; Pope, C; Murray, E; Atherton, H (Elsevier, 2021)
Despite widespread acknowledgement of internet use for information about health, patients report not disclosing use of online health information in consultations. This paper compares patients’ reported use of the internet with matched video recordings of consultations. The concepts of doctorability and epistemics are employed to consider similarities and differences between patients’ reports in interviews and actions in the consultation.